EXTERNAL FRICTION OF MATERIALS OF FRICTION ASSEMBLIES OF BRAKING DEVICES - Вольченко, Дмитрий Александрович; Киндрачук, Мирослав Васильевич; Скрыпнык, Василий Степанович; Журавлев, Дмитрий Юрьевич; Малык, Владимир Якович; Андрейчиков, Евгений Юрьевич (Problems of Friction and Wear, 2021)
In the materials of the article, the tribological subsystems of various types of frictional units of brakes are considered; performance parameters and structural adaptability of materials of friction pairs of braking devices; energy levels and principles of structural adaptability of friction pair materials. The work function of particles from the microprotrusions of the friction surfaces of metal-polymer interfaces is estimated depending on the specific load, sliding speed and surface temperature, taking into account the energy levels of the surface layers of the friction pair, observing the principles of structural adaptability of their materials. It is shown that the excess entropy generated on the rubbing surfaces of the brake devices plays a negative role if Kf >> KT (where Kf and KT are the kinematic constants of chemical reactions). On the basis of the studies performed, regularities of the formation of the characteristics of processes, phenomena, and effects at the hierarchical levels of textures of the materials of the tribo-conjugate contacts under their electrothermomechanical frictional loading are proposed. On the basis of the performed studies, the regularities of the formation of the characteristics of processes, phenomena and effects at the hierarchical levels of textures of the materials of the tribo-conjugate contacts under their electrothermomechanical frictional loading are proposed, expressed in the following: the regularities of the formation of characteristics of processes, phenomena and effects at the hierarchical levels of textures of materials of contacts of tribo-conjugation during their electrothermomechanical frictional loading is expressed in the following: Previously unknown regularities of the formation of characteristics of processes, phenomena and effects at unstable hierarchical levels of electrothermomechanical loading in triboconjugation were established, observing the principles of structural adaptability with an increase in the total entropy of the surface layers of its materials with a simultaneous decrease in their free energy and being in an elastic-plastic state , consisting in the fact that under the influence of mechanical, electrical and thermal fields of a pulsed nature, as well as chemical fields, areas of spots of microprotrusions, which are contacts with different properties, surface layers of structures of materials that have crystal lattices in transversely and longitudinally oscillating electrons and ions with nonlocal the responses of its structure to changes in specific loads, due to the simulation of repeating composite matrices in the near-surface and underlying layers of material materials, spherical and short cylindrical inclusions oriented parallel and perpendicular to the friction surfaces, reducing the deformation components and being T-shaped energy bridges, allowing to achieve a quasi-identical energy loading of the surface layers by removing excess generated energy into the higher and lower layers with different thicknesses, which ensures their identical wear, and the ongoing transformations on the areas of contact spots of microprotrusions, implemented quasi-adequately with the predicted aperiodicity of repetitive processes, phenomena and effects at nano, micro and milli-level in compliance with the quantitative principles of superposition "decrease - increase" and "increase - decrease" of their characteristics, as well as the principles of superposition concerning the processes, phenomena and effects that are accompanied by "expansion (heating) - compression (cooling)", as well as at the same rate of their flow, "recovery - destruction" and "softening - strengthening", reproducing the primary and in toric texture with films of various types on the contact spots for the same period of time as a result of the implementation of various technological methods of strengthening the surface areas of a friction metal element under aperiodic modes of electrothermomechanical loading of tribo-conjugation. "